Kampanye Public Relations Dalam Membangun Public Awareness Pencegahan Tuberkulosis di Wilayah Jakarta Timur (Studi Deskriptif Kualitatif Yayasan Pejuang Tangguh) - Chaer Ranie Cahyaningsih; Tria Patrianti (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study is motivated by the persistently high incidence of Tuberculosis in Indonesia, particularly in densely populated urban areas such as East Jakarta. Tuberculosis prevention efforts are not solely dependent on medical interventions but also require effective communication strategies to increase public awareness. This study aims to analyze the public relations campaign conducted by Yayasan Pejuang Tangguh in building public awareness regarding Tuberculosis prevention in East Jakarta. This research employed a descriptive qualitative method, with data collected through in-depth interviews with the Case Manager and Patient Support staff of Yayasan Pejuang Tangguh. The findings indicate that Yayasan Pejuang Tangguh demonstrates key characteristics of a public relations campaign, including the freedom of audiences in receiving campaign messages, the perceived benefits experienced by both campaign implementers and audiences, and the use of various campaign techniques. These activities play a significant role in enhancing public awareness of Tuberculosis prevention.